The Effect of FDI to Accelerate the Economic Growth of Bangladesh and Some Problems & Prospects of FDI - Faruk, Mohammad Omar (Asian Business Review, 2013)
Foreign Direct Investment (FDI) has great impact on the development of a developing country like Bangladesh. The foreign investor seeks for new sources of investment where the developing country seeks for new sources of fund to develop the country. The FDI does not only bring sources of fund in a developing country but also new technology in a developing country. The FDI has the important role to develop the garments & weaving, telecommunication, banking and pharmaceuticals industry of Bangladesh. In this paper the role of FDI in economic growth (GDP) is analyzed to find out relationship between FDI and GDP in Bangladesh. To analyze the impact, The GDP has been taken as a dependent and FDI as an independent variable to run the regression analysis where the result shows that the FDI can explain about 83% data of GDP, p value much less than 0.05 to reject null hypothesis and GDP changes 64.0709 units for changes of each unit of FDI. The correlation matrix shows the GDP and FDI is highly correlated (0.912024962) in perspective of Bangladesh economy, so the FDI has grater impact on GDP or Economic Growth of Bangladesh. Some of the problems and prospects of FDI in Bangladesh is also discussed in the paper.JEL Classification Code: F21